PTEN loss defines a TGF-β-induced tubule phenotype of failed differentiation and JNK signaling during renal fibrosis - Lan, Rongpei; Kriz, Wilhelm (American journal of physiology. Renal physiology, 2012)
We investigated the signaling basis for tubule pathology during fibrosis after renal injury. Numerous signaling pathways are activated physiologically to direct tubule regeneration after acute kidney injury (AKI) but several persist pathologically after repair. Among these, transforming growth factor (TGF)-β is particularly important because it controls epithelial differentiation and profibrotic cytokine production. We found that increased TGF-β signaling after AKI is accompanied by PTEN loss from proximal tubules (PT). With time, subpopulations of regenerating PT with persistent loss of PTEN (phosphate and tension homolog) failed to differentiate, became growth arrested, expressed vimentin, displayed profibrotic JNK activation, and produced PDGF-B. These tubules were surrounded by fibrosis. In contrast, PTEN recovery was associated with epithelial differentiation, normal tubule repair, and less fibrosis. This beneficial outcome was promoted by TGF-β antagonism. Tubule-specific induction of TGF-β led to PTEN loss, JNK activation, and fibrosis even without prior AKI. In PT culture, high TGF-β depleted PTEN, inhibited differentiation, and activated JNK. Conversely, TGF-β antagonism increased PTEN, promoted differentiation, and decreased JNK activity. Cre-Lox PTEN deletion suppressed differentiation, induced growth arrest, and activated JNK. The low-PTEN state with JNK signaling and fibrosis was ameliorated by contralateral nephrectomy done 2 wk after unilateral ischemia, suggesting reversibility of the low-PTEN dysfunctional tubule phenotype. Vimentin-expressing tubules with low-PTEN and JNK activation were associated with fibrosis also after tubule-selective AKI, and with human chronic kidney diseases of diverse etiology. By preventing tubule differentiation, the low-PTEN state may provide a platform for signals initiated physiologically to persist pathologically and cause fibrosis after injury.
Gesehen am 18.10.2018